PENGARUH NON PERFORMING FINANCING, TINGKAT BAGI HASIL, MODAL SENDIRI DAN DAN DANA PIHAK KETIGA TERHADAP PEMBIAYAAN BAGI HASIL PADA PERBANKAN SYARIAH - Dila Anggraini; Indra Iman Sumantri (EkoPreneur, 2019)
The purpose of this study is the results of the Profit Sharing Funds, Own Capital and Third Party Funds for Profit Sharing Financing. This study uses secondary data for the 2014-2018 period in Islamic banking. The sampling technique uses purposive sampling. Tool for processing data using SPS 21.0. The results showed that Non Performing Financing had no effect on Profit Sharing Financing, Profit Sharing Levels did not have a significant positive effect on Profit Sharing Financing, Own Capital did not have a significant effect on Profit Sharing Financing, Funds Keywords: Non Performing Financing, Profit Sharing Rate, Own Capital, Third Party Funds, Profit Sharing Financing.